1999
DOI: 10.1128/jvi.73.2.1080-1091.1999
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Activity of the AU-Rich RNA Element in the Human Papillomavirus Type 1 Late 3′ Untranslated Region Correlates with Its Affinity for the elav-Like HuR Protein

Abstract: A 57-nucleotide adenosine- and uridine-rich RNA instability element in the human papillomavirus type 1 late 3′ untranslated region termedh1ARE has previously been shown to interact specifically with three nuclear proteins that failed to bind to an inactive mutant RNA. Two of those were identified as the heterogeneous ribonucleoproteins C1 and C2, whereas the third, a 38-kDa, poly(U) binding protein (p38), remained unidentified. Here we show that partially purified p38 reacts with a monoclonal antibody raised a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 53 publications
(106 reference statements)
0
22
0
1
Order By: Relevance
“…HuR and U2AF 65 both bind to the late UTR of HPV-31 [Cumming et al, 2002], HuR also binds to the AU-rich instability element in HPV-1 [Sokolowski et al, 1997[Sokolowski et al, , 1999 and U2AF 65 to a negative regulatory element in HPV-16 [Koffa et al, 2000]. The expression profile for these proteins would support a role in inhibiting late gene expression.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…HuR and U2AF 65 both bind to the late UTR of HPV-31 [Cumming et al, 2002], HuR also binds to the AU-rich instability element in HPV-1 [Sokolowski et al, 1997[Sokolowski et al, , 1999 and U2AF 65 to a negative regulatory element in HPV-16 [Koffa et al, 2000]. The expression profile for these proteins would support a role in inhibiting late gene expression.…”
Section: Discussionmentioning
confidence: 98%
“…It has been demonstrated that a number of cellular RNA-binding proteins interact with regulatory RNA elements on HPV mRNAs, the late mRNAs in particular. It has been shown for example, that hnRNP C1/C2 and HuR interact with an AU-rich RNA instability element in the late 3 0 UTR of HPV-1 [Sokolowski et al, 1997[Sokolowski et al, , 1999Sokolowski and Schwartz, 2001], CstF64, U2AF 65 and HuR along with ASF/SF2 bind to a negative element within the HPV-16 late UTR RNA [Dietrich-Goetz et al, 1997;Koffa et al, 2000;McPhillips et al, 2004], and that the late UTR of HPV-31 interacts with CstF64, HuR and U2AF 65 [Cumming et al, 2002]. In addition hnRNP A1 was shown to bind to multiple splicing silencers in the HPV-16 L1 coding region thereby inhibiting splicing of the late mRNAs [Zhao et al, 2004], hnRNP K and poly(rC) binding proteins interact with inhibitory elements within HPV-16 L2 reducing the expression of the late genes [Collier et al, 1998], and hnRNP H binds to motifs within HPV-16 L2 promoting the use of the early polyadenylation signal .…”
Section: Introductionmentioning
confidence: 99%
“…HeLa cell nuclear extracts were prepared according to the method of Dignam et al (1983). GST-hnRNP A1 was prepared as described previously (Sokolowski et al, 1999). Twenty micrograms of nuclear extract or fifty nanograms of recombinant hnRNP A1 was used for each UV cross-linking.…”
Section: Uv Cross-linking and Preparation Of Cellular Extracts And Rementioning
confidence: 99%
“…Mutant mice lacking TTP develop cachexia, arthritis and autoimmunity as a consequence of overexpressed TNF‐α mRNA and protein (Taylor et al ., 1996). In addition to TTP, Hel‐N1 (Levine et al ., 1993), HuR (Myer et al ., 1997; Fan and Steitz, 1998; Peng et al ., 1998; Sokolowski et al ., 1999), AUF1 [heterogeneous nuclear ribonucleoprotein (hnRNP) D] (Zhang et al ., 1993) and TIAR (Gueydan et al ., 1999) are ARE‐binding proteins that have been proposed to regulate the expression of TNF‐α (Sakai et al ., 1999). Hel‐N1 (Levine et al ., 1993; Gao et al ., 1994; Ford et al ., 1999) and HuR (Myer et al ., 1997; Fan and Steitz, 1998; Peng et al ., 1998; Sokolowski et al ., 1999) stabilize ARE‐containing transcripts, whereas AUF1 destabilizes these transcripts (Loflin et al ., 1999).…”
Section: Introductionmentioning
confidence: 99%